2014
DOI: 10.1890/13-0390.1
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐lake experiments reveal the fate of terrestrial particulate organic carbon in benthic food webs of shallow lakes

Abstract: Abstract. Lake ecosystems are strongly linked to their terrestrial surroundings by material and energy fluxes across ecosystem boundaries. However, the contribution of terrestrial particulate organic carbon (tPOC) from annual leaf fall to lake food webs has not yet been adequately traced and quantified. In this study, we conducted whole-lake experiments to trace artificially added tPOC through the food webs of two shallow lakes of similar eutrophic status, but featuring alternative stable regimes (macrophyte r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 54 publications
(74 reference statements)
0
31
0
Order By: Relevance
“…Terrestrial inputs to freshwater food webs, as suggested by stable isotopes, are viewed as subsidies that contribute a significant fraction of the trophic base for animals , Bartels et al 2012, Scharnweber et al 2014). We found considerable use of a terrestrial subsidy by insects, crustaceans, reptiles, and fishes, largely originating with pasture grasses that use the C 4 photosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Terrestrial inputs to freshwater food webs, as suggested by stable isotopes, are viewed as subsidies that contribute a significant fraction of the trophic base for animals , Bartels et al 2012, Scharnweber et al 2014). We found considerable use of a terrestrial subsidy by insects, crustaceans, reptiles, and fishes, largely originating with pasture grasses that use the C 4 photosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…). tPOM derived from the catchment area can sediment before reaching the pelagic areas of lakes, and thus, can be more important in littoral than in pelagic food webs (Scharnweber et al ). It is also possible that LC–SAFA are not efficiently assimilated or they are preferentially excreted by zooplankton, which would make them unsuitable as biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted whole‐lake experiments as part of an unrelated project starting in October 2010 (Scharnweber et al. , Mehner et al. ), for which both lakes were divided in an east‐west direction by a plastic curtain, producing fully isolated, equally sized halves.…”
Section: Methodsmentioning
confidence: 99%